An application of incremental running test results to train professional soccer players - Radziminski, L.; Rompa, P.; Dargiewicz, R.; Ignatiuk, W.; Jastrzebski, Z. (Baltic Journal of Health and Physical Activity, 2010)
Background: The aim of this study was to lay out an incremental running test to determine anaerobic threshold and its usefulness as a predictability factor of the physiological load on professional soccer players during soccer training activities.